2020
DOI: 10.1177/1055665620921669
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Adjustment of Children Born With a Cleft Lip and/or Palate: Cross-Sectional and Longitudinal Analyses

Abstract: Objective: To determine the psychosocial adjustment of children born with a cleft lip and/or palate (CL/P). Design: Longitudinal analyses of psychosocial outcomes and cross-sectional comparison with published norms. Setting: Retrospective clinical audit at a UK cleft center. Participants: Data available for 1174 participants born with a CL/P at ages 5 (n = 658), 10 (n = 415), and 15 (n = 171), with longitudinal data for a subset of the sample at 5 and 10 (n = 168) and 10 and 15 (n = 49). Main Outcome Measure: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(55 reference statements)
4
14
0
Order By: Relevance
“…Although all groups trended in the lower half of the average range, this difference was only consistently significant for those with iCLP. This is consistent with previous studies that have found psychosocial functioning to be within the broad average range, but increased risk based on age or gender (Hunt et al, 2005; Wolodiger & Pope, 2019; Pinckston et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Although all groups trended in the lower half of the average range, this difference was only consistently significant for those with iCLP. This is consistent with previous studies that have found psychosocial functioning to be within the broad average range, but increased risk based on age or gender (Hunt et al, 2005; Wolodiger & Pope, 2019; Pinckston et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of more parent-reported conduct problems among children with OFC is in concordance with an early study suggesting increased prevalence of externalizing problems in children with OFC (Millard & Richman, 2001;Richman et al, 2012) and with a recent longitudinal study using the SDQ in which at age 5 children with CL/P had higher reported conduct problems, although these were not present at ages 10 and 15 years (Pinckston et al, 2020). It has also been shown in NZ, using the SDQ in young children (3½ years of age), that there is a high prevalence of externalizing problems; however, this is no longer present by 7 years of age (Cornforth, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…In a UK study, Waylen et al (2017) reported that the only difference between 5-year-old children with cleft and controls was the presence of higher hyperactivity scores and that there were no differences associated with self-confidence, facial differences, or behavior (Waylen et al, 2017). A longitudinal analysis of parent reported difficulties on the Strengths and Difficulties Questionnaire found that at ages 5 and 10 years children with CL/P had elevated total difficulties scores relative to the normative sample although these effect sizes were small as assessed using a continuous score (Pinckston et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Increased hyperactivity-related difficulties, but not other behavioural problems, were found in 6-12 year old children born with cleft from the United States (Wehby et al, 2012). In addition, a recent longitudinal study reported increased behavioral difficulties, as measured by the SDQ at ages 5 and 10 years, with boys born with cleft reporting more difficulties (Pinckston et al, 2020). Emotional difficulties and deficient social competencies have also been found in school-aged children born with cleft (Murray et al, 2010;Waylen et al, 2017).…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
“…Children born with CL/P typically present with subclinical mental health and wellbeing needs , which are negatively impacted when the cleft is combined with additional conditions and stresses . Evidence from longitudinal and cross-sectional studies suggests that children born with CL/P present with behavioural problems at ages 5 and 10 years more frequently than children without CL/P in the general population (Pinckston, Dalton, Farrar, & Hotton, 2020;Waylen et al, 2017). However, large-scale individual studies on clinical populations are rare, and more research is required to ascertain the prevalence of mental health problems and to examine the possible unmet needs of this group (Berger & Dalton, 2011;Feragen, Saervold, Aukner, & Stock, 2017;Klassen et al, 2012;Thomas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%